From intention to behavior: analytical model of doctor’s moral hazard behavior-based on planned behavior theory - Wang, Yaohui; He, Lina; Liu, Quanlong; Li, Xinchun (Acta Bioethica, 2020)
Based on the concept of doctor’s moral hazard behavior and the theoretical model of planned behavior, this paper constructs a theoretical model of doctor’s moral hazard behaviorm and analyzes the main influencing factors of doctor’s moral hazard behavior in detail, including behavioral attitudes, subjective norms and perceived behavioral control. Combined with the results of questionnaire survey, this paper uses structural equation model and factor analysis to verify the hypotheses. The results show that in the theoretical model of doctor’s moral hazard behavior, doctors’ moral risk intentions are affected by three independent variables: behavioral attitudes, subjective norms and perceived behavioral control. As an intermediary variable, moral risk intentions have a mediating effect on doctors’ moral hazard behavior. All path coefficients meet the requirements, and all assumptions of the model are verified. The theoretical model of doctor’s moral hazard behavior established in this study can effectively explain the occurrence law of doctor’s moral hazard behavior and can predict doctor’s moral hazard behavior according to the actual situation of various influencing factors. This provides an effective theoretical guidance for the next step to better carry out the relevant research on doctor’s moral hazard based on the management perspective, especially the establishment of prevention and control strategies for doctor’s moral hazard behavior.